Momentum Isra Mi’raj sebagai Penguat Ketauhidan dan RAT sebagai Solusi Permasalahan Koperasi: Isra Mi'raj Momentum as a Strengthening of Knowledge and RAT as a Solution to Cooperative Problems - Pawestri, Aprilia Indah Dwi; Rahmawati, Diah Fajar; Khairunnisa, Nurul Izzah; Syar'i, Ahmad; Khalfiah, Yuliani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
At the Amanah 'Aisyiyah Palangka Raya Cooperative, several problems were encountered. So, a Final Annual Meeting was held as a means of obtaining solutions to each problem. The meeting was attended by all cooperative members and UMS KKN-dik students. Through this activity, KKN-dik students become aware of the various problems faced by the community in the cooperative. So, through this discussion forum, students try to help provide solutions related to the problems they face using the mediation method. This is done by students as a form of community service. Apart from that, community service activities were also carried out in the form of recitations using community education methods that took advantage of the momentum of the Isra Mi'raj. This activity involved collaboration with the Aisyiyah Regional Leadership and was attended by all Aisyiyah members. Apart from the aim of commemorating Isra Mi'raj, the recitation was carried out to study in more depth the history, benefits and sins of leaving prayer. So the hope is that all listeners of the study will pray better. The importance of the two types of community service activities that have been carried out are improving the welfare and improving the physical condition of the community through the Amanah 'Aisyiyah Cooperative which provides opportunities for residents who want to dedicate themselves in the way of Allah through a community that is guided by the Koran and helps the economy of cooperative members. It is hoped that these two activities will have a positive impact on society.